SISTEM INFORMASI PENERIMAAN DAN PENGELUARAN KAS PADA PUTRA BUANA (BERBASIS VB) - Agustin, Riska; Upayarto, Budi (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2024)
The study aims to analyze, design and also implement a cash receipt and disbursement information system at Putra Buana. The research method used was design using the waterfall development method with research instruments consisting of field studies including observations and interviews, as well as literature studies. The analysis method used was PIECES analysis, as well as system requirements analysis, the software used was Microsoft Visual Studio 2010 and information reports using Crystal Report. System testing was carried out using black-box testing techniques. The test results show that the functions that have been created have worked as expected. The system can make easier to enter data, prepare financial reports or other needs, and also maintain the integrity and accuracy of data.